2017
DOI: 10.3183/npprj-2017-32-03-p317-323
|View full text |Cite
|
Sign up to set email alerts
|

The effect of increased pulp yield using additives in the softwood kraft cook on the physical properties of lowgrammage handsheets

Abstract: ABSTRACT:The effect of increasing the pulp yield by the addition of sodium borohydride (NaBH 4 ) or polysulfide (PS) in softwood kraft cooking, i.e. enhancing the retention of glucomannan, on the physical properties of low-grammage handsheets was studied. In addition to the yield improvement, an increase in tensile index was observed, especially at lower degrees of beating. These higher yield pulps showed an increase in pore volume, indicating an increased degree of swelling of the fibres. Presumably, the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…This result may be explained by the higher hemicelluloses contents of the pulps derived from kraft-PS cooking. Our results corroborated with those from Rahman et al, [10] which observed an increasing in tensile index for spruce pulp due to the use of PS as additive in kraft cooking, especially at lower refining degrees. It is worth noting that the well-known correlation between tensile and burst strength did not hold true when the proportion of pine fibers in the furnish increased.…”
Section: Pulp Refinability Drainability and Qualitysupporting
confidence: 93%
See 3 more Smart Citations
“…This result may be explained by the higher hemicelluloses contents of the pulps derived from kraft-PS cooking. Our results corroborated with those from Rahman et al, [10] which observed an increasing in tensile index for spruce pulp due to the use of PS as additive in kraft cooking, especially at lower refining degrees. It is worth noting that the well-known correlation between tensile and burst strength did not hold true when the proportion of pine fibers in the furnish increased.…”
Section: Pulp Refinability Drainability and Qualitysupporting
confidence: 93%
“…[13,34] Nevertheless, there are also chemical aspects of carbohydrate preservation by PS, especially hemicelluloses, which need to be considered. [8][9][10] The results in Table 2 shows that there is, in general, a greater preservation of the hemicelluloses in the pulps for the PS assisted cooking, although this trend is not so clear when the charge of PS is increased from 1.5 to 3.0%. The PS brought more significant benefits for the wood chip mixture containing larger proportion of pine chips, which is explained by the PS protection of the mannans, which are labile during kraft pulping and exist in larger quantities in the softwoods.…”
Section: Ps Cooking Of Wood Mixturesmentioning
confidence: 96%
See 2 more Smart Citations
“…An unbeaten low grammage handsheet of 20 gm/m 2 was measured for single line scanning in this setup. The low grammage handsheet 20 gm/m 2 was prepared by mixing CTMP and BSWK at different percentages according to the ISO 5269-2:2004 standard with tap water using a conventional sheet former with a surface area of 0.021 m 2 at the SCA R&D Centre in Sundsvall, Sweden . For the study of sulfonation degree, four different proportions as 100% CTMP, 50% CTMP + 50% BSWK, 30% CTMP + 70% BSWK, and 20% CTMP + 80% BSWK were used.…”
Section: Methodsmentioning
confidence: 99%